Passivity in Implant-Supported Prosthesis - Monteiro, Douglas Roberto [UNESP]; Goiato, Marcelo Coelho [UNESP]; Gennari Filho, Humberto [UNESP]; Pesqueira, Aldieris Alves [UNESP] (Lippincott Williams & Wilkins, 2010)
Because of the widespread use of implant-supported restorations and that the success of this treatment depends on the passivity of the different component systems of implant-prosthesis, a literature review was performed to highlight issues related to passivity in framework of implant-supported fixed prosthesis. A search of English-language peer-review literature was completed using MEDLINE database (PubMed) focusing on acceptable levels of passivity, misfit classification, problems related to misfit, methods to evaluate misfit, general factors that affect the passivity, and the biologic tolerance in the presence of misfit. The information obtained in the present review suggested that even if it is hard to obtain an implant-supported prosthesis with complete passivity, the professional should use the technological resources to offer better conditions for their patients. An acceptable clinical level of passivity that does not cause any problem to the biologic, aesthetic, and functional parameters of the patient should be sought.
Keywords: Dental implants; prosthetic fit; prosthetic misfit